Pengaruh Penggunaan Subtitusi Pozolan Dan Penambahan Serat Karet Ban Bekas Kendaraan Terhadap Kuat Tarik Belah Beton Normal - Imransyah Idroes; Fikri Harli; Bunyamin (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2022)
Used tires are one of the largest contributors to inorganic material wasted, as a result of the rapidly increasing growth of vehicles. The use of waste tires as a substitute material or as an enhancer in a concrete mixture reduces the level of environmental pollution. The quality of the plan on the concrete plan is f'c 17 MPa is the minimum requirement for structural concrete in SNI 2847-2019. This study was conducted on 20 test objects measuring 15 x 30 cm, 15 test objects using 5%, 10%, and15% used vehicle tire fiber and 10% pozzolana, while for comparison, 5 pieces of normal concrete test objects were used. The method used in this study was to use SNI 03-2491-2002, SNI 2460-2014, SNI 2847-2019, ACI 2.11.1-91, and ASTM C 618-03. The tensile strength of normal concrete is 2.44 MPa and its variations are 2.34 MPa, 2.27 MPa, and 2.23 MPa, respectively. The ratio of the tensile strength of compressive strength to the normal concrete specimens, materials, and designs and their corresponding variations is 13.34%, 19,14%, 19,19%, and 20,52%. As well as the ratio of tensile strength of split and normal concrete of 17 MPa in a row is 13.37%, 13.34%, and 13.09%.